Obama's Afghan arm-twisting : weakening Karzai to give him strength? - Lorimore, Clint (2009)
The Obama administration's public criticism of Afghan President Hamid Karzai in recent weeks has spareked a great deal of speculation that it is looking to back an alternative candidate in Afghanistan's upcoming elections. However this move may be part of a diplomatic strategy to both spur Karzai into making uncomfortable political changes while simultaneously giving him the distance to re-generate his image.